Selective cyclooxygenase-2 inhibitors show a differential ability to inhibit proliferation and induce apoptosis of colon adenocarcinoma cells - Yamazaki, Ryuta; Kusunoki, Natsuko; Matsuzaki, Takeshi; Hashimoto, Shusuke; Kawai, Shinichi (FEBS letters, 2002)
Although the influence of selective cyclooxygenase (COX)-2 inhibitors on the proliferation of colon adenocarcinoma cells have been the subject of much investigation, relatively little research has compared the effects of different COX-2 inhibitors. Celecoxib strongly suppressed the proliferation of COX-2 expressing HT-29 cells at 10–40 μM. NS-398 and nimesulide also inhibited cell proliferation, whereas rofecoxib, meloxicam, and etodolac did not. Only celecoxib induced apoptosis of HT-29 cells, as detected on the basis of DNA fragmentation, TUNEL positivity, and caspase-3/7 activation. DNA fragmentation was also increasd in COX-2 non-expressing cell lines (SW-480 and HCT-116) by exposure to celecoxib for 6–24 h. All six COX-2 inhibitors suppressed the production of prostaglandin E 2 by HT-29 cells, suggesting that the pro-apoptotic effect of celecoxib was unrelated to inhibition of COX-2. Inactivation of Akt might explain the differential pro-apoptotic effect of these selective COX-2 inhibitors on colon adenocarcinoma cells.